Question

229-3(8+6)-9(6-2)

156

likes778 views

Corbin

4.6

86 Answers

1. Evaluate the expressions inside the parentheses:

8 + 6 = 14 and 6 - 2 = 4

2. Substitute these values back into the expression:

229 - 3(14) - 9(4)

3. Perform the multiplications:

3 \times 14 = 42 and 9 \times 4 = 36

4. Substitute these values back into the expression:

229 - 42 - 36

5. Perform the subtractions step-by-step:

229 - 42 = 187

187 - 36 = 151

2. Substitute these values back into the expression:

3. Perform the multiplications:

4. Substitute these values back into the expression:

5. Perform the subtractions step-by-step:

Frequently asked questions (FAQs)

What is 2.5 as a percent?

+

What is the value of sin(45°) + cos(60°) / tan(30°)?

+

Find the roots of the cubic equation x^3 + 2x^2 - 3x - 2 = 0.

+

New questions in Mathematics